A relação público-privado na educação infantil no município de Goiânia: da trajetória legal da política pública de convênios à percepção dos atores-gestores envolvidos - Branco, Nicássia Alves Cezário (2019)
The aim of the research, the public-private relationship in the education of children in the city of Goiania: from the legal trajectory of the public policy of covenants to the perception of the actorsmanagers involved, was to understand how the policy of agreements for children's education in the city of Goiânia is constituted and to recognize the perception of the actors-managers involved. As a theoretical background, we highlight the works of Anderson (1995); Giddens (2005); Peroni (2013); Peroni and Scheibe (2017); Mundim e Silva (2017); Di Pietro (2017); Adrião (2018), among others. In addition to national and municipal legislation, we bring the Master Plan for the Reform of the State Apparatus (BRASIL, 1995a); the National Education Guidelines and Framework Law nº 9.394/1996; National Curricular Guidelines for Early Childhood Education (BRASIL/MEC, 2009b); Law No. 13,019/2014; Public Notice No. 001/2018 (GOIÂNIA/SEMAD, 2018), among others. In order to reach the proposed objectives, the qualitative approach was used, since it allows an analysis rich in descriptive details, both bibliographical and documentary research. The research was divided into three phases: 1) exploratory phase; 2) fieldwork phase; 3) phase of analysis and treatment of collected data. The exploratory phase consisted of the search for literature dating from the Federal Constitution of 1988. The second phase was characterized by semi-structured interviews. Finally, in the third and last phase, the empirical and documentary data of this research were analyzed under the light of the theoretical background. In this way, we verified that the policy of agreements for early childhood education in the city of Goiânia was constituted in 1999, due to the process of municipalization of state daycare centers. At the time, the Term of Agreement was formalized between the SME of Goiânia and the Civil Society Organizations (OCS), under the modality of technical-financial cooperation, totaling sixty-four (64) partner institutions. However, according to data provided by the SME of Goiânia in September 2017, this amount has changed over the years. There was a decrease in the number of institutions in the technical-financial modality, from sixty-four (64) to eight (08) institutions, while thirty-five (35) became financial cooperation and the remainder (21) has migrated to total agreement, which demonstrates an increase in the form of financial cooperation. In detriment of Federal Law No. 13,019/2014, the Agreement Contract of SME Goiânia was replaced by the Term of Collaboration in January 2018, when the participation of non-profit OSC began to happen through a Public Call, as established by this law. Hence, the number of financial cooperation institutions that had their proposals approved was only seventeen. Regarding the perception of managing agents, we recognize the strengthening of partnerships with the third sector, coming from a policy that aims to disclaimer the government structure of the obligation to promote basic public services to third-country citizens, which we also characterize the agreements/term of collaboration as a way of camouflaging the privatization of public education.